Diagnóstico sobre el sistema de dirección estratégica en las empresas líderes de la provincia de Sancti Spíritus - López Concepción, Arelys (Universidad Central "Marta Abreu" de Las Villas, 2007)
The assimilation of the Strategic Direction in the cuban managerial system shows attachment to the internacional sphere in this field. Nevertheless after a decade of its introduction it can be seen deficiencies that solutions need to be given. In order to consolidate the application of a system which demonstrated advantages. For this reason, in the present paper a diagnosis is done, in order to know the Strategic Direction behavior in the main companies of Sancti Spiritus province. So as to optain a more complete information about the performance and function of such program and to contribute to improve its attention. There were carried out different tools in this investigation. To get the information a survey was applied, documents were cheked and the statistical process through the SPSS. As a result of the study it could be seen that the Strategic Direction is a process that is taking part in the main companies of Sancti Spiritus province that denotes the need to find a greater mastery in the system´s options because the main directors underestimate its kindness in such a way, that is why it is necessary to develop ways of qualifying and of strategic acting that fallow and control the process appliance.
Keywords: Dirección Estratégica; Sancti Spíritus; Diagnóstico; Empresas